A highly decoupled transmit–receive array design with triangular elements at 7T. Issue 5 (23rd March 2018) - Chen, Gang; Zhang, Bei; Cloos, Martijn A.; Sodickson, Daniel K.; Wiggins, Graham C.
Abstract : Purpose: Transmit arrays are essential tools for various RF shimming or parallel excitation techniques at 7T. Here we present an array design with triangular coils to improve diversity in the B1 profiles in the longitudinal ( z ) direction and allow for next‐nearest neighbor decoupling. Methods: Two cylindrical 8‐channel arrays having the same length and diameter, 1 of triangular coils and the other of rectangular coils, were constructed and compared in phantom imaging experiments using measures of excitation distribution for a variety of RF shim settings and geometry factor maps for different accelerations on different planes. Results: Coupling between elements was −20 dB or better for all triangular coil pairs, but worse than −12 dB for several of the rectangular coil pairs. Both coils could produce adequate shims on a central transverse plane, but the same shim produced worse results off center for the triangular coil array than for the rectangular coil array. Compared to the rectangular coil array, the maximum geometry factor for the triangular coil array was reduced by a factor of 13.1 when using a 2‐fold acceleration in the z ‐direction. Conclusion: An array design with triangular coils provides effective decoupling mechanisms for nearest and next‐nearest neighboring elements, as well as diversity in B1 profiles along the z ‐direction, although this also means that individual slices must be shimmed separately. This design is well suited for parallel transmit applications while also having high receive sensitivity.